Comparing the Optical Coherence Tomography Outcomes of Intravitreal Injection Anti Vascular Endothelial Growth Factor in Branch Retinal Vein Occlusion (BRVO) - Sandri; Weni Helvinda (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2023)
Background: BRVO is a blockage of the branches of the retinal vein due to a thrombus. The prevalence of 10-year BRVO is 1.6 per 100 subjects. The effect of anti-VEGF injection on BRVO management is effective in improving visual acuity and reducing macular oedema. Case presentation: A man, 32 years old, presented to the ophthalmology clinic at the Dr. M. Djamil General Hospital with a chief complaint of blurred vision in his left eye 1 week before admission. The blurred vision began suddenly. Visual acuity in LE was 20/50 and did not advance with a pinhole. Funduscopic examination of LE showed clear media, rounded papillae with well-defined borders, blood vessels aa:vv = 1:3, venous tortuosity (+) increased in the inferotemporal quadrant; retina: Bleeding (+) with dot blot and flame-shaped inferiorly, exudate (+) cotton wool spots at the inferotemporal region; foveal reflex (+)↓ on the macula. OCT LE examination showed macular intraretinal hypo-reflection and macular thickening with a central macular thickness of 617 μm. The physical examination showed a body weight of 114.9 kg, a height of 173 cm, and a body mass index of 38.4. Within 5 months after 3 times administrations of intravitreal injections of anti-VEGF bevacizumab and ranibizumab, visual acuity of LE: 20/25 was obtained, and increased appearance of the retinal fundus and OCT LE. Conclusion: Intravitreal injection therapy of anti-VEGF bevacizumab and ranibizumab is effective in reducing macular oedema and restoring visual acuity in BRVO.